Congenital cystic adenomatoid malformation of lung: A case report - Banerjee, Asish; Pal, Sumita; Chatterjee, Anish; Pan, A (Journal of College of Medical Sciences-Nepal, 2015)
A term neonate developed respiratory distress after 12 hours of birth which was diagnosed as a case of congenital cystic adenomatoid malformation (CCAM) of the right lung by computerized tomography scan. CCAM of the lung is rare congenital cystic lung lesion. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12767 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 41-42